The Relationship Between Premenstrual Syndrome and Mood Swings Based on Questionnaires SPAF and FDMS in Faculty Students Third Year of Medicine - Ratu Fathya Aulia Putri; Sadya Wendra; Herin Setianingsih; Prajogo Wibowo (Journal of Social Research, 2026)
Premenstrual Syndrome (PMS) is a collection of physical, emotional, and behavioral symptoms that appear during the luteal phase and can affect daily activities, including academic and emotional functioning. This study aims to determine the relationship between PMS and mood changes based on the SPAF and FDMS questionnaires among third-year Faculty of Medicine students. This study uses an observational analytical design with a cross-sectional approach and was conducted at the Faculty of Medicine, Hang Tuah University, Surabaya. Primary data were obtained through the distribution of the Shortened Premenstrual Assessment Form (SPAF) questionnaire to assess PMS levels and the Four-Dimensional Mood Scale (FDMS) to measure mood conditions. The results showed that most respondents experienced moderate PMS (55.3%) and were in a fairly good mood (82.5%). Bivariate analysis using the Spearman correlation test showed a significant association between PMS and mood changes (p < 0.001), with a negative relationship and a weak–moderate correlation strength (r = ?0.379). This indicates that the more severe the level of PMS, the worse the mood tends to be. The conclusion of this study is that there is a relationship between the level of PMS and mood changes based on the SPAF and FDMS questionnaires among third-year Faculty of Medicine students. These findings underscore the importance of promotive and preventive efforts, including education on PMS management, stress management, and reproductive health monitoring to support the physical and emotional well-being of female students.